PENERAPAN AKUNTANSI PERTANGGUNG JAWABAN DENGAN ANGGARAN SEBAGAI ALAT PENGENDALIAN BIAYA PADA PT. PERTANI (PERSERO) UNIT PENGGILINGAN PADI (UPP) KABUPATEN SIDENRENG RAPPANG - Ady S; Abdul Azis (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the application of accounting for responsibility, cost control, and the role of accounting for responsibility in supporting the efficiency of cost control at PT. Pertani (Persero) Rice Milling Unit of Sidenreng Rappang Regency. The data collection techniques used in this study are interviews, observations, and documentation. Informants in the study are the chairman, the financial treasurer, and the material treasurer. The data analysis technique used in this study is qualitative analysis. The results of the study obtained that the application of accounting with the budget as a cost control tool at PT. Pertani (Persero) Rice Milling Unit of Sidenreng Rappang Regency has been adequate.